2009
DOI: 10.1007/978-3-642-04968-2_4
|View full text |Cite
|
Sign up to set email alerts
|

A Labeled Data Set for Flow-Based Intrusion Detection

Abstract: Flow-based intrusion detection has recently become a promising security mechanism in high speed networks (1-10 Gbps). Despite the richness in contributions in this field, benchmarking of flow-based IDS is still an open issue. In this paper, we propose the first publicly available, labeled data set for flowbased intrusion detection. The data set aims to be realistic, i.e., representative of real traffic and complete from a labeling perspective. Our goal is to provide such enriched data set for tuning, training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 13 publications
0
80
0
5
Order By: Relevance
“…Unfortunately, as this dataset has appeared recentlym, we had no chance to use it in our studies. Interesting flow-based traffic dataset has been recently made publicly available by Sperotto et al [115]. This set is based on data collected from a real honeypot (monitored trap) featuring HTTP, SSH and FTP services.…”
Section: Origin Of the Ideamentioning
confidence: 99%
“…Unfortunately, as this dataset has appeared recentlym, we had no chance to use it in our studies. Interesting flow-based traffic dataset has been recently made publicly available by Sperotto et al [115]. This set is based on data collected from a real honeypot (monitored trap) featuring HTTP, SSH and FTP services.…”
Section: Origin Of the Ideamentioning
confidence: 99%
“…Although the attack is very common, it is still potentially dangerous. Our studies [4] showed that newly set up vulnerable hosts can be compromised within few days and be used as platform for the same attacks. We also showed that SSH attacks are visible at flow level as peaks in the SSH flow time series [20].…”
Section: Related Workmentioning
confidence: 82%
“…In most cases, a ground truth is missing. Attack-labeled flow data sets are rare and their creation is a lengthy and time consuming process [4]. To overcome this problem, approaches based on the superposition of real non-malicious traffic with synthetic attack traffic have been introduced [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the KDD Cup 99 dataset [4], and the other one is a data set taken from [5,6], which is the `University of Twente in September 2008' dataset.…”
Section: Resultsmentioning
confidence: 99%